A facile signal-on electrochemical DNA sensing platform for ultrasensitive detection of pathogenic bacteria based on Exo III-assisted autonomous multiple-cycle amplification. Issue 9 (22nd March 2019) - Pei, Qianqian; Song, Xiaolei; Liu, Su; Wang, Jingfeng; Leng, Xueqi; Cui, Xuejun; Yu, Jinghua; Wang, Yu; Huang, Jiadong
Abstract : A facile signal-on electrochemical DNA biosensor for ultrasensitive detection of pathogenic bacteria based on Exo III-assisted autonomous multiple-cycle amplification. Abstract : A facile signal-on electrochemical DNA biosensor has been developed for ultrasensitive detection of pathogenic bacteria using an Exo III-assisted autonomous multiple-cycle amplification strategy. The strategy relies on pathogens and aptamer binding-initiated release of a trigger, which combines with the 3′-protruding terminus of the hairpin probe 1, leading to the formation of double-stranded DNA with a blunt 3′ terminus which starts the Exo III-assisted multiple signal amplification reaction. In addition, hairpin probe 2 labeled with an electroactive reporter at the middle of the loop region is ingeniously designed to contain a short hairpin-embedded segment, which can fold into a hairpin structure via an Exo III-assisted cleavage reaction, thus bringing the redox molecule in proximity to the electrode surface for "signal-on" sensing. Under optimal conditions, this biosensor exhibits a very low detection limit as low as 8 cfu mL −1 and a wide linear range from 1.0 × 10 1 to 1.0 × 10 7 cfu mL −1 of target pathogenic bacteria. As far as we know, this is the first time that the Exo III-assisted autonomous multiple-cycle amplification strategy has been used for signal-on electrochemical sensing of pathogenic bacteria. In addition, the proposed sensor can also be used for highly sensitive detection of other targets by changing the aptamer sequence, such as nucleic acids, proteins and small molecules. Therefore, the proposed signal-on electrochemical sensing strategy might provide a simple and practical new platform for detection of pathogenic bacteria and related biological analysis, food safety inspection and environmental monitoring.